Feasible permutations of Kepler's spheres - Ong, Artemis P. (Animo Repository, 1997)
Kepler's spheres are twelve spheres which are tangential to a central sphere. The main concern of this study is to consider a related question of Erno Rubik: if we label the twelve spheres and roll them over the surface of the inner sphere at will, what permutations are achievable? . This thesis shows how the concepts in group theory and geometry may be applied to determine the feasible permutations of Kepler's spheres. The article by James G. Propp entitled Kepler's Spheres and Rubik's Cube served as a basic material in developing this paper.